Preposition à la in Public Discourse of German Language - E. L. Shubina; A. V. Averina (Научный диалог, 2024)
The functioning of the French-origin preposition à la in the modern journalistic corpus of the German language is analyzed. The relevance of the study is due to the lack of linguistic description of this preposition in domestic and foreign German studies, despite its productivity in the German language. Combinations including the preposition à la were identified through a comprehensive sampling method in the DWDS corpus. The authors consider the preposition as synonymous with German derived prepositions that denote “similarity, likeness”: nach Art von, im Stile von, in der Art von, nach dem Prinzip von. It is noted that proper names (à la Agatha Christie) and predicative units (à la “Klinsmann liebt Leipzig”) serve as the main carriers of the preposition, with fewer examples involving concrete, abstract, and animate nouns. A paradigm of variable government for this preposition is proposed. The authors conclude that the choice of case government for the preposition is influenced by the structural characteristics of prepositional constructions, namely the presence / absence of an article or accompanying word after the preposition, as well as the gender and number of the governed noun.